Impact of the Audio-Visual Learning Method on the Development of Foreign Language Communication Competence of Future Interpreters and Translator - Sobol, Tetiana (Educational Challenges, 2021)
This article purpose is to concern the importance of applying a communicative approach to learning a foreign language by future interpreters and translators. The communicative approach creates situations that are as close as possible to the peculiarities of the real process of communication. Therefore, the object of this study can be considered the didactic process of communicative competence formation of future interpreters and translators. This approach is aimed at paying more attention to the functions of language, lexical and grammatical units, which contributes to the development of communicatively oriented mastery of educational material by future interpreters and translators. The author has established the fact that thanks to a communicative approach, future interpreters and translators will be able to master foreign language communicative competence, which is necessary for orientation in the cultural aspect of a foreign language. There was used the methodology of interdisciplinary research such as analysis of scientific sources and educational materials. It confirmed that a foreign language communicative competence includes a system of knowledge and skills necessary for the effective use for a foreign language in professional and intercultural spheres. It is especially important for interpreters and translators, who must always know the language situation and know the cultural specifics of a foreign nation. Therefore, the result of this study can be considered as the following. The most effective way to achieve this goal is audiovisual reproduction of the linguistic and cultural situation, because standards of foreign language samples can come to our mind and can stay in long-term memory only with audio and visual perception. In addition, image and visual support is important not only for the semantic understanding of individual words or expressions, but also for the correct transmission of all content. Conclusion: the audiovisual method of learning a foreign language is one of the most effective for the foreign language communicative competence formation for future interpreters and translators.